Soil Organic Matter Temperature Sensitivity Cannot be Directly Inferred From Spatial Gradients. Issue 6 (26th June 2019) - Abramoff, Rose Z.; Torn, Margaret S.; Georgiou, Katerina; Tang, Jinyun; Riley, William J.
Abstract: Developing and testing decadal‐scale predictions of soil response to climate change is difficult because there are few long‐term warming experiments or other direct observations of temperature response. As a result, spatial variation in temperature is often used to characterize the influence of temperature on soil organic carbon (SOC) stocks under current and warmer temperatures. This approach assumes that the decadal‐scale response of SOC to warming is similar to the relationship between temperature and SOC stocks across sites that are at quasi steady state; however, this assumption is poorly tested. We developed four variants of a Reaction‐network‐based model of soil organic matter and microbes using measured SOC stocks from a 4, 000‐km latitudinal transect. Each variant reflects different assumptions about the temperature sensitivities of microbial activity and mineral sorption. All four model variants predicted the same response of SOC to temperature at steady state, but different projections of transient warming responses. The relative importance of Q max, mean annual temperature, and net primary production, assessed using a machine‐learning algorithm, changed depending on warming duration. When mineral sorption was temperature sensitive, the predicted average change in SOC after 100 years of 5 °C warming was −18% if warming decreased sorption or +9% if warming increased sorption. When microbial activity was temperature sensitive but mineral sorption was not, average site‐level SOC loss was 5%. We conclude that spatial climate gradients of SOC stocks are insufficient to constrain the transient response; measurements that distinguish process controls and/or observations from long‐term warming experiments, especially mineral fractions, are needed. Key Points: Spatial climate gradients are insufficient for inferring transient temperature response of soil carbon decomposition and stocks The temperature sensitivity of both microbial activity and mineral sorption has large effects on SOC response More comprehensive data, including SOC in mineral fractions, from long‐term warming experiments may help distinguish between model assumptions